Influence of Fly Ash and Emery based particulate reinforced AA7075 surface composite processed through friction stir processing. (August 2022) - Suganeswaran, K.; Parameshwaran, R.; Sathiskumar, R.; Ram Prabhu, T.; Nithyavathy, N.
The novel friction stir technology is adopted in modern automotive industries to meet the desired properties like hardness, impact toughness and tribological behaviour over the conventional techniques like stir casting, compo casting, squeeze casting, electroplating and infiltration methods. AA7075 surface composites fabricated with different volume fractions of fly ash and emery particles is said to enhance the aforementioned properties. The composites are processed through friction stir process (rotational speed −1200 rpm, transverse speed – 56 mm/min, tool tilt angle – 2 °). During characterization, the Microstructural examination of surface composites depicts fine and homogenous distribution of reinforcements in the friction stir process region owing to severe plastic deformation and dynamic recrystallization process. Substantially, good interface is formed between the reinforcement particulates and base substrate. Inclusion of Fe3 O4, Al2 O3 and SiO2 constituents through fly ash and emery reinforcements associated with the homogenous dispersion strengthening mechanism favours for the superior hardness of surface hybrid composite specimen 50E50FA. Decremented grain size and load bearing capacity of the reinforcements is beneficial for the crack propagation resistance that enhances the impact toughness behaviour (17.4 J/cm 2 ) of the same specimen. Wear rate of the specimens are evaluated through pin on disc tribometer. The decrease in the wear rate of hard specimen 50E50FA is observed due to the reduced contact area between its surface and counter disc. The morphology of worn specimens using SEM analysis shows the combined abrasive and adhesive wear as the worn mechanism.